Does the cowl make the monk? The effect of military and Red Cross uniforms on empathy for pain, sense of agency and moral behaviors - Pech, Guillaume P.; Caspar, Emilie A. (Frontiers in Psychology, 2023)
According to the embodied cognition framework, cognitive functions are not confined to the brain but are also shaped by the mutual interactions between the brain, body, and external environment. In this regard, a theory developed in 2012, called enclothed cognition, suggests an effect on wearing specific clothing on various psychological processes. However, the neuro-cognitive mechanisms underlying the impact of clothing on behavior have received less systematic investigation. The present study examined the influence of clothing on prosocial behaviors, and focused on sense of agency, and empathy for pain as neuro-cognitive processes of interest. Participants (40 in total) wore civilian, military, and Red Cross uniforms. They were paired up and assigned as either agents or victims. Agents had the option to administer real electric shocks to victims for a monetary reward of +€0.05. They could choose to shock freely (free condition) or follow the experimenter's instructions (coerced condition). We measured prosocial behavior by counting the number of shocks prevented, neural empathic response using electroencephalography with the P3 and the LPP, and sense of agency through an implicit method based on interval estimates. Findings showed that wearing the Red Cross uniform led to more prosocial behavior compared to civilian clothing. The Red Cross uniform also increased neural response to pain when participants witnessed shocks, compared to civilian or military clothing. Moreover, wearing a military uniform increased the sense of agency in the free condition, as compared to civilian clothing. This study broadens our knowledge on the impact of enclothed cognition on cognitive and psychological processes.